Four inputs-one output fuzzy logic system for washing machine - Nurain Zulaikha Husin; Muhammad Zaini Ahmad; Mustafa Mamat (Institute of Advanced Engineering and Science, 2022)
The presence of fuzzy logic system on washing machine becomes a demand in every home as it simplifies human work. The uses of washing machine will facilitate the user, reduce electricity consumption, washing time and water intake. Thus, in this paper, fuzzy logic system is used to determine the washing time by considering four different inputs, which are type of fabric, type of dirt, dirtiness of fabric and weight of load. The possible rules from the input variables are developed by combining all the variables using fuzzy IF-THEN rule. Referring to the Mamdani inference engine, a minimum membership function from input parts is truncated to the output for each of the rules. Next, the maximum membership function from the output is aggregated and the washing time can be calculated by using centroid method. The comparison is done by comparing the washing time of four input variables with three input variables.